2017
DOI: 10.1002/rmb2.12030
|View full text |Cite
|
Sign up to set email alerts
|

Thin endometrium transcriptome analysis reveals a potential mechanism of implantation failure

Abstract: AimAlthough a thin endometrium has been well recognized as a critical factor in implantation failure, little information is available regarding the molecular mechanisms. The present study investigated these mechanisms by using genome‐wide mRNA expression analysis.MethodsThin and normal endometrial tissue was obtained from a total of six women during the mid‐luteal phase of the menstrual cycle. The transcriptomes were analyzed with a microarray. Differentially expressed genes were classified according to Gene O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 35 publications
(93 reference statements)
4
33
0
Order By: Relevance
“…Maekawa et al [ 27 ] found an aberrant Th1-pro-inflammatory/Th2-anti-inflammatory balance and increased cytotoxic condition in patients with thin endometrium. Genome-wide mRNA expression analysis was used in order to show the different expression profiles that exist in case of patients with thin endometrium compared to the control group with an endometrium ≥7 mm [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maekawa et al [ 27 ] found an aberrant Th1-pro-inflammatory/Th2-anti-inflammatory balance and increased cytotoxic condition in patients with thin endometrium. Genome-wide mRNA expression analysis was used in order to show the different expression profiles that exist in case of patients with thin endometrium compared to the control group with an endometrium ≥7 mm [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although no significant enrichment was observed, it was noteworthy that four out of 18 DEGs were related to “cytoskeleton organization” ( MNS1, TTLL1 , TPPP , UGT8 ). Interestingly, UGT8 was down-regulated in the endometrium of women affected by implantation failure [ 54 ]. The gene FCER1A is associated with “positive regulation of granulocyte macrophage colony-stimulating factor production” was less expressed in NB-pregnant heifers.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing our results with the atlas of the RNA editome in Sus scrofa skeletal muscle [78], we confirmed 22 of 57 RNA editing sites expressed in the endometrial tissues. Significant AAF changes in 3 UTR TMEM161A and upstream from GFM1 could be linked with the potential mechanism of implantation failure [79] and intrauterine growth retardation [80], respectively. SNV-calling methods are valuable tools which expand our understanding of post-transcriptional modifications in the porcine genome.…”
Section: Discussionmentioning
confidence: 99%